Pemberdayaan Masyarakat melalui Pengaplikasian Teknologi Balur Apung untuk Mengatasi Keterbatasan Lahan Pertanian di Daerah Aliran Sungai Desa Tanjong Sangalang, Pulang Pisau: Community Empowerment through the Application of Floating Raft Technology to Overcome Agricultural Land Limitations in the River Basin Area of Tanjong Sangalang Village, Pulang Pisau - Kurniawati, Neny; Arifin, Samsul; Andanu, Odi; Dirgantara, Made (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The floating raft technology presents an innovative solution to address the flooding challenges that frequently disrupt agriculture in Tanjung Sanggalang Village, Pulang Pisau Regency. With this technology, floating farming on water surfaces becomes feasible, allowing the land to be no longer affected by floods and enabling farmers to utilize it more effectively, thereby increasing overall agricultural production. Floating raft technology aims to help improve food security and the economy of the Tanjung Sanggalang community by expanding agricultural areas and enhancing crop production. The community service methods include Focus Group Discussions (FGD), material presentations, hands-on practice, and evaluation. The results of the community service show that the practical training on floating raft construction was highly beneficial to all participants. The training met participants' expectations, with 100% of participants reporting that their expectations were fulfilled. Therefore, the training on floating raft construction, seedling, organic fertilizers, pesticides, and harvesting has been successfully conducted.